Antioxidant effect of Arabic gum against mercuric chloride-induced nephrotoxicity - Gado AM; Aldahmash BA (Dove Medical Press, 2013)
Ali M Gado,1 Badr A Aldahmash21Forensic Medicine and Clinical Toxicology Department, College of Medicine, Tanta University, Tanta, Egypt; 2Medical Laboratory Department, College of Health Sciences, King Saud University, Riyadh, Saudi ArabiaAbstract: The effects of Arabic gum (AG) against nephrotoxicity of mercury (Hg), an oxidative-stress inducing substance, in rats were investigated. A single dose of mercuric chloride (5 mg/kg intraperitoneal injection) induced renal toxicity, manifested biochemically by a significant increase in serum creatinine, blood urea nitrogen, thiobarbituric acid reactive substances, and total nitrate/nitrite production in kidney tissues. In addition, reduced glutathione, glutathione peroxidase, and catalase enzymes in renal tissues were significantly decreased. Pretreatment of rats with AG (7.5 g/kg/day per oral administration), starting 5 days before mercuric chloride injection and continuing through the experimental period, resulted in a complete reversal of Hg-induced increase in creatinine, blood urea nitrogen, thiobarbituric acid reactive substances, and total nitrate/nitrite to control values. Histopathologic examination of kidney tissues confirmed the biochemical data; pretreatment of AG prevented Hg-induced degenerative changes of kidney tissues. These results indicate that AG is an efficient cytoprotective agent against Hg-induced nephrotoxicity by a mechanism related at least in part to its ability to decrease oxidative and nitrosative stress and preserve the activity of antioxidant enzymes in kidney tissues.Keywords: mercury, acacia gum, oxidative stress, lipid per oxidation, kidney toxicity